Pengaruh Kecerdasan Emosional Dan Beban Kerja Terhadap Kinerja Perawat Instalasi Rawat Inap RSUD Bangil - Anjali, Bella Permata; Ismail, Iriani (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This study aims at determining the effect of emotional intelligence and workload on the performance of inpatient nurses at Bangil Regional Public Hospital. This study employed a quantitative study with a total sample of 59 nurses. This study uses quantitative research methods and sampling techniques in this study using random sampling techniques. Data collection techniques used were interviews, questionnaires, and documentation. The data analysis technique used was validity and reliability test, classic assumption test, regression analysis, and hypothesis testing. Based on the research analysis being carried out, the results showed that (1) Emotional intelligence has a positive and significant effect on performance (2) Workload has a negative and significant effect on performance  (3) Emotional intelligence and workload simultaneously have a positive and significant effect on the performance